2020
DOI: 10.1111/1759-7714.13574
|View full text |Cite
|
Sign up to set email alerts
|

DLL3 expression is a predictive marker of sensitivity to adjuvant chemotherapy for pulmonary LCNEC

Abstract: Background The mammalian Notch family ligands delta‐like 3 (DLL3) is reported to be a potential therapeutic target for large cell neuroendocrine carcinomas (LCNEC). The effect of DLL3 expression on LCNEC prognosis has not yet been elucidated. Methods We reviewed the medical records of 70 LCNEC patients undergoing surgical resection between 2001 and 2015 using a prospectively maintained database. We performed immunohistochemistry for DLL3 and investigated the correlation between the sensitivity of LCNEC to plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
4
14
0
Order By: Relevance
“…However, we did not observe this association in high-grade tumors, which confirms previous results from the literature ( 29 ). In accordance with previous reports ( 29 , 37 ), we observed a significant correlation between higher DLL3 expression and increased staining intensity of chromogranin A in high-grade tumors, which supported the hypothesis that the DLL3 expression is related to NE differentiation and could promote NE tumorigenesis in high-grade lung NETs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, we did not observe this association in high-grade tumors, which confirms previous results from the literature ( 29 ). In accordance with previous reports ( 29 , 37 ), we observed a significant correlation between higher DLL3 expression and increased staining intensity of chromogranin A in high-grade tumors, which supported the hypothesis that the DLL3 expression is related to NE differentiation and could promote NE tumorigenesis in high-grade lung NETs.…”
Section: Discussionsupporting
confidence: 93%
“…The association between high DLL3 expression and lower OS and DFS suggests that this marker might be associated with more aggressive tumors, even if this association has not been confirmed for high-grade tumors. The high proportion of patients with positive DLL3 tumor expression, despite the absence of prognostic implications, confirms previous results in SCLC and LCNEC patients ( 28 , 37 39 ). A study by Huang et al.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…DLL3 expression is a potential therapeutic target for DLL3 targeting agent. One such agent is Rovalpituzumab-tesirine (Rova-T) a DLL3 targeting antibody drug conjugate (139,141,142). Rova-T was evaluated in a phase 1 study and then a phase 2 study which confirmed antitumor activity but was notable for a high percentage of a patients with adverse events (141,143).…”
Section: Future Directionsmentioning
confidence: 99%